Effects of Targeted Versus Adjustable Protein Fortification of Breast Milk on Early Growth in Very Low‐Birth‐Weight Preterm Infants: A Randomized Clinical Trial. (25th April 2019) - Bulut, Ozgul; Coban, Asuman; Uzunhan, Ozan; Ince, Zeynep
Abstract: Background: Breast milk is preferred for the feeding of very low‐birth‐weight (VLBW) infants, but it does not meet nutrition requirements unless it is fortified. Adequate protein intake to maintain the growth of preterm infants cannot be provided by standard fortification methods because of variation in the protein content of human milk. Individualization is necessary to achieve target protein intakes. The goal of this study was to compare the effects of 2 different methods of individualized protein fortification of breast milk on the early growth of VLBW preterm infants. Methods: In a prospective observational study, VLBW preterm infants ≤32 weeks of gestational age were randomized into 2 groups according to the method of breast milk fortification. Anthropometric measurements were performed in both groups weekly for 4 weeks to compare their growth. Results: During the trial period, the daily protein intake (targeted vs adjustable fortification groups) was (median [range]) 4.5 (4.4–4.6) vs 4.01 (3.5–4.4) g/kg/d ( P  = 0.001); the daily weight gains (g/d and g/kg/d; mean ± SD) were 25.7 ± 3.9 vs 22.2 ± 6.4 g/d ( P  = 0.048) and 23.1 ± 4.3 vs 18.7 ± 4.3 g/kg/d ( P  = 0.014); and the weekly increase in head circumference was 9.8 ± 1.5 vs 8.4 ± 2.1 mm/wk ( P  = 0.040). All parameters were significantly higher in the targeted than the adjustable fortification group. Conclusions: Individualized protein fortification using the targeted method for VLBW preterm infants had more positive effects on short‐term growth compared with the adjustable fortification method.